RADIKALISME DAN PENYIMPANGAN IDEOLOGI GERAKAN SALAFI - Rozi, Achmad Bahrur (STAIN Kediri, 2017)
The emergence of issues of Islamic radicalism is a new challenge for Muslims in the middle of the global association. Salafi s have been identifi ed as radical Islamic movements because they think that Islam is not just religion but ideology as well. This article tries to answer the question whether Islam, as a belief system, gave birth to the ideological seeds of violence and terror? What is the ideal relationship between Islam and ideology, how is the linkage of radicalism with the Islamic movement called the Salafi s? and what is exactly the ideological deviation of the Salafi movement? Key words: Radicalism, Ideology, Salafi